PECVD synthesis, optical and mechanical properties of silicon carbon nitride films - Ermakova E. N. Evgeniya Nikolaevna; Rumyantsev Y. M. Yurii Mihailovich; Shugurov A. R. Artur Rubinovich; Panin A. V. Alexey Viktorovich; Kosinova M. L. Marina Leonidovna (2015, 2015)
Title screen